Headache management: pharmacological approaches. Issue 6 (3rd July 2015) - Sinclair, Alex J; Sturrock, Aaron; Davies, Brendan; Matharu, Manjit
Abstract : Headache is one of the most common conditions presenting to the neurology clinic, yet a significant proportion of these patients are unsatisfied by their clinic experience. Headache can be extremely disabling; effective treatment is not only essential for patients but is rewarding for the physician. In this first of two parts review of headache, we provide an overview of headache management, emerging therapeutic strategies and an accessible interpretation of clinical guidelines to assist the busy neurologist.